Concept of the journal “Mining of Mineral Deposits” of the National Mining University - Bondarenko, V.; Lozynskyi, V.; Kovalevska, I.; Sai, K.; Vvedenska, T. (Розробка родовищ, 2016)
This article describes the present concept of the journal “Mining of Mineral Deposits”. The introduction features information about the Underground Mining Department where the journal was created. It also focuses on a short prehistory of creating Ukrainian “School of Underground Mining”. Special consideration is given to previous journals and scientific and technical collections issued by the Department. The scope of topics and the details about the journal reformatting are also provided.